Effect of Silica Sodalite Loading on SOD/PSF Membranes during Treatment of Phenol-Containing Wastewater - Olawumi O. Sadare; Rivoningo Ngobeni; Michael O. Daramola (Membranes, 2022)
In this study, silica sodalite (SSOD) was prepared via topotactic conversion and different silica sodalite loadings were infused into the polysulfone (PSF) for application in phenol-containing water treatment. The composite membranes were fabricated through the phase inversion technique. Physicochemical characteristics of the nanoparticles and membranes were checked using a Scanning Electron Microscope (SEM), Brunauer Emmett–Teller (BET), and Fourier Transform Infrared (FTIR) for surface morphology, textural properties, and surface chemistry, respectively. A nanotensile test, Atomic Force Microscopy (AFM), and contact angle measurement were used to check the mechanical properties, surface roughness, and hydrophilicity of the membranes, respectively. SEM results revealed that the pure polysulfone surface is highly porous with large evident pores. However, the pores decreased with increasing SSOD loading. The performance of the fabricated membranes was evaluated using a dead-end filtration device at varying feed pressure during phenol-containing water treatment. The concentration of phenol in water used in this study was 20 mg/L. The pure PSF displayed the maximum phenol rejection of 95 55% at 4 bar, compared to the composite membranes having 61.35% and 64.75% phenol rejection for 5 wt.% SSOD loading and 10 wt.% SSOD loading, respectively. In this study, a novel Psf-infused SSOD membrane was successfully fabricated for the treatment of synthetic phenol-containing water to alleviate the challenges associated with it.